2020
DOI: 10.1016/j.aim.2020.107141
|View full text |Cite
|
Sign up to set email alerts
|

GKM theory and Hamiltonian non-Kähler actions in dimension 6

Abstract: Using the classification of 6-dimensional manifolds by Wall, Jupp andŽubr, we observe that the diffeomorphism type of simply-connected, compact 6-dimensional integer GKM T 2 -manifolds is encoded in their GKM graph. As an application, we show that the 6-dimensional manifolds on which Tolman and Woodward constructed Hamiltonian, non-Kähler T 2 -actions with finite fixed point set are both diffeomorphic to Eschenburg's twisted flag manifold SU(3)//T 2 . In particular, they admit a noninvariant Kähler structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The following theorem was proven in [16]. Namely, it was proven in [16] that Tolman's manifold is diffeomorphic to Eschenburg's manifold.…”
Section: The Diffeomorphism Type Of M Tmentioning
confidence: 98%
See 3 more Smart Citations
“…The following theorem was proven in [16]. Namely, it was proven in [16] that Tolman's manifold is diffeomorphic to Eschenburg's manifold.…”
Section: The Diffeomorphism Type Of M Tmentioning
confidence: 98%
“…The following theorem was proven in [16]. Namely, it was proven in [16] that Tolman's manifold is diffeomorphic to Eschenburg's manifold. On the other hand, Eschenburg's manifold is diffeomorphic to the projectivisation of a rank 2 bundle over CP 2 [12,Theorem 2].…”
Section: The Diffeomorphism Type Of M Tmentioning
confidence: 98%
See 2 more Smart Citations
“…Tolman [17] and Woodward [19] constructed a six-dimensional closed Hamiltonian T 2 -manifold with only isolated fixed points and with no T 2 -invariant Kähler metric. Surprisingly Goertsches-Kostantis-Zoller [10] have recently shown that the examples of Tolman and Woodward indeed admit Kähler metrics that are not T 2 -invariant. Thus their result provides a positive evidence for the conjecture of the existence of Kähler metrics.…”
Section: Introductionmentioning
confidence: 99%